Pelatihan, Dan Pendampingan Pembuatan Konten Youtube Tutorial Bagi Remaja Masjid Nurul Hidayah Sebagai Sarana Pengembangan Industri Kreatif - Pratiwi, Iqlima; Putra, Arda Purnama; Arafik, Muh; Andajani, Kusubakti (STIE Malangkucecwara, 2023)
Social media, which was originally intended as a two-way interactive communication medium, is now opening up new opportunities in creative industry innovation. It is necessary to develop creative industries related to society's potential through interesting YouTube content with the help of efficient technology. One of the youth groups in Malang Regency is the Nurul Hidayah Mosque Youth. The priority problems agreed upon with the Nurul Hidayah Mosque Youth to be addressed through the Community Partnership Program are: (1) Social Media Literacy and (2) Creative Industry Development. Based on the results of the meeting and joint coordination with the Nurul Hidayah Mosque Youth as Community Partnership Program Partners, it was agreed that the above problems would be resolved using the following methods: (1) Social Media Literacy which includes: Education and training: exploring interest in creating potential YouTube content and media literacy social. (2) Creative Industry Development which includes: Education, training and assistance: creating a YouTube account, recording video tutorials using the Camtasya application, editing video tutorials, and uploading YouTube videos. The contribution of the Nurul Hidayah Mosque Youth is providing support in the form of: adjusting electrical power, providing electrical installation network to ensure that the equipment to be handed over can operate optimally and lay out the production site.